141k views
3 votes
Use the function below to find f(-2).

F(x)= 3^x

A. 1/6
B. -9
C. -6
D. 1/9

Use the function below to find f(-2). F(x)= 3^x A. 1/6 B. -9 C. -6 D. 1/9-example-1
User DooDoo
by
5.2k points

1 Answer

2 votes

Answer:

D. 1/9

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation
  • Exponential Rule [Rewrite]:
    \displaystyle b^(-m) = (1)/(b^m)

Explanation:

Step 1: Define

Identify

f(x) = 3ˣ

f(-2) is x = -2 for function f(x)

Step 2: Evaluate

  1. Substitute in x [Function f(x)]: f(-2) = 3⁻²
  2. Exponents: f(-2) = 1/9
User Kustomrtr
by
5.5k points